2006
DOI: 10.1007/s10663-006-9001-4
|View full text |Cite
|
Sign up to set email alerts
|

Conditional correlations in the returns on oil companies stock prices and their determinants

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Empirical findings of their multivariate cointegration and vector error correction models (VECM) confirmed the statistical significance of the major financial variables in explaining the long-run dynamics of oil company stock values. Giovannini et al (2006) studied financial risk factors and several integrated oil company stock price returns based on VECM and DCC-GARCH methods. The financial risk factors include stock market indices, foreign exchange rates, and the difference between the 12-month futures price and spot price on the Brent oil spread.…”
Section: Determinants Of Stock Returns Of Oil and Gas Companiesmentioning
confidence: 99%
“…Empirical findings of their multivariate cointegration and vector error correction models (VECM) confirmed the statistical significance of the major financial variables in explaining the long-run dynamics of oil company stock values. Giovannini et al (2006) studied financial risk factors and several integrated oil company stock price returns based on VECM and DCC-GARCH methods. The financial risk factors include stock market indices, foreign exchange rates, and the difference between the 12-month futures price and spot price on the Brent oil spread.…”
Section: Determinants Of Stock Returns Of Oil and Gas Companiesmentioning
confidence: 99%
“…Additionally, Osmundsen et al (2006) found that the major determinants of firm valuation are oil price, oil and gas production, and to a certain extent, reserve replacement. To examine the relationship between stock prices returns and financial risk factors of oil companies, Giovannini et al (2006) used multivariate cointegration techniques and multivariate GARCH Model. In an earlier study, Quirin et al (2000) identified reserve replacement, reserves growth, production growth, and finding costs as the major factors of equity valuation.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Gogineni (2010) determined a significant influence of the price of crude oil on markets which are not immediately related to the oil industry. Giovannini et al (2004) found a number of important dependencies between companies in the oil industry. Bhardwaj and Dunsby (2012) concluded that the relationships between commodity markets and the stock market vary according to the phase of the business cycle.…”
Section: Literature Reviewmentioning
confidence: 99%